Risk factors for mortality in prostatic abscess: Insights into patient characteristics and drainage practices - Yun-Chen Tsai; Jian-Ri Li; Chiann Yi Hsu; Che-An Tsai (PLoS ONE, 2026)
Prostatic abscess, which is an uncommon urinary tract disease, can lead to mortality if not properly treated. This retrospective study aimed to identify risk factors associated with mortality in patients with prostatic abscess, with the goal of providing insights to improve clinical outcomes. The study was conducted on patients diagnosed with prostatic abscess and hospitalized between January 2007 and December 2021. The diagnosis was confirmed through imaging. Out of 822 hospitalized patients with acute prostatitis or prostatic abscess, 102 had prostatic abscess (12.4%). The mean age was 68.8 years old, and overall mortality was 8.8%. Drainage was performed in 15.7% cases. There was no significant difference in abscess size, prostate volume, or percentage of abscess formation at other sites between survivors and non-survivors. Age and use of alpha blockers were identified factors related to death, and older age remained significantly related to mortality (OR=1.07) in multivariate analysis. Factors associated with drainage or transurethral resection of the prostate were analyzed. Abscess size (OR=1.70), cystostomy (OR=4.56), prostate volume (OR=1.01) and the presence of abscess in other organs (OR=3.89) were associated with drainage, whereas abscess size (OR=1.58), cystostomy (OR=5.13), and liver cirrhosis (OR=5.67) were associated with transurethral resection of prostate. There were no differences between the drainage and non-drainage groups after propensity score matching for age, BMI, and abscess size. In our study, advanced age was the primary factor associated with mortality in patients with prostate abscess. Other factors, including drainage and abscess size, were not significantly associated with mortality; however, these findings may be influenced by confounding factors and the limited number of mortality events, warranting further investigation.